Repetitive Control in the Applications of H-Bridge Active Power Filter - Yang Liu; Guojun Tan (Institute of Advanced Engineering and Science, 2013)
In order to improve the deficiency of the traditional repetitive control, a novel control method combining dead beat control and repetitive control in series is proposed to improve the dynamic performance of the control system. A low-pass filter on the delay link of repetitive control is added to solve the contradiction between repetitive control stability and steady-state accuracy, while the compensation link is designed with the combination of leading phase and the low-pass filter to reduce the control object by relying on accurate mathematical model. The control method, on the basis of steady state accuracy, improves the relative speed and compensation accuracy. The feasibility of the proposed method is verified by the experimental design. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2838